SARS-CoV-2: Combating Coronavirus Emergence - Graham, Rachel L. (Immunity, 2020)
The emergence and rapid global spread of SARS-CoV-2 mark the third such identification of a novel coronavirus capable of causing severe, potentially fatal disease in humans in the 21(st) century. As noted by Andersen et al. (Nature Medicine), the sequencing of proximal zoonotic ancestors to SARS-CoV-2 has aided in the identification of alleles that may contribute to the virus’ virulence in humans.